Transformation of Physics Learning Approaches in the Digital Era: A Systematic Literature Study on Curriculum Adaptation and Innovation in Vocational Education - Santi Septiana Zarita; Cut Liliiza Yusra; Ferdiansyah Novriza; Herdian Saputra (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
Vocational education institutions in Indonesia face growing pressure to realign physics learning with the demands of Industry 4.0, yet a comprehensive synthesis of how digital curriculum adaptation occurs in this specific context remains limited. This study aims to examine patterns of digital transformation in physics learning approaches, analyze responsive curriculum adaptation strategies, evaluate implemented digital innovations, and formulate strategic recommendations for vocational physics education in Indonesia. A qualitative library research method was employed, with data collected from academic publications indexed in Google Scholar and SINTA, spanning the period 2020–2024. Articles were selected based on inclusion criteria covering relevance to digital physics learning, vocational education context, and publication quality, resulting in ten studies subjected to content analysis and source triangulation. Findings indicate that technologies such as HTML5-based digital comics, STEM gamification, and Arduino microcontroller-based teaching aids have demonstrably improved student engagement and academic outcomes. Responsive curriculum adaptation requires systematic integration of problem-based learning and project-based learning supported by digital technology. Implementation gaps persist between ideal conditions and actual practice, necessitating strategic interventions in educator professional development, industry-academia partnerships, and technology infrastructure investment. This study contributes a holistic analytical framework for understanding the interrelation between technological innovation, curriculum adaptation, and learning outcomes in Indonesian vocational education.